Determinant of Capital Efficiency and Its Impact on Economic Growth: Empirical Evidence in East Java - Dwi Budi Santoso; Agus Suman (Signifikan: Jurnal Ilmu Ekonomi, 2023)
East Java is the engine of Indonesia’s economic growth. Nevertheless, this region is still faced with the performance of industrial development, which has yet to increase consistently, thereby worsening efficiency and economic growth. As a result, this paper aims to investigate the causes and consequences of capital efficiency in the context of East Java. This paper produces three results by employing the 3SLS simultaneous equation estimation method. First, this paper demonstrates that industrial development in East Java improves efficiency. Second, improving the education level has a positive effect on capital efficiency. Lastly, an increase in capital inefficiency leads to a negative effect on economic growth in East Java. This study suggests three key policies for accelerating economic growth in East Java: providing incentives to industries that can increase capital efficiency, developing innovations to increase capital efficiency, and improving education quality to encourage increased human resource productivity.JEL Classification: D24, O14, O4How to Cite:Santoso, D. B., & Suman, A. (2023). Determinant of Capital Efficiency and Its Impact on Economic Growth: Empirical Evidence in East Java. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 1-10. https://doi.org/10.15408/sjie.v12i1.29965.